E-commerce : business on the Internet - McLaren, Constance H.; McLaren, Bruce J. (Cincinnati : South-Western Educational, 2000)
This book is about: An introduction to electronic commerce; Personal and business services online; Byuing online; Doing business on the Web; Developing an electronic commerce Web site; ...
Keywords: Internet; Business; Electronic commerce; Electronic commerce